(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2023)
Introduction In qualitative research, reflexivity is a cornerstone for enhancing the rigor and trustworthiness of investigations focused on exploring personal and professional narratives. The works of scholars like Van der Riet (2012) highlight the critical role of reflexivity in qualitative research by underscoring its impact on the inquiry into meaning and practice within individuals’ life stories. Malterud (2011) further emphasizes that researchers’ backgrounds and perspectives inevitably influence various stages of the research process, from topic selection to communication of findings. This underscores the importance of being reflexive for effective research outcomes. In this discourse, I reflect upon my own transformative journey as I grappled with my initial aversion to qualitative research and how embracing reflexivity has altered my outlook and shaped my research perspective. Personal Journey and Transition My introduction to qualitative research was met with skepticism, influenced by my past experiences and training in quantitative research. As someone less involved in research, my initial inclination leaned toward disliking the process. Nevertheless, as I delved into qualitative research literature and participated in class discussions, I began to appreciate the value of its methodologies. The shift from quantitative to qualitative research marked a turning point in my research journey. I realized that my role extended beyond being a mere researcher; I had to understand my place in the social context, be aware of my limitations, and cultivate a heightened sensitivity to nuances and interactions. Embracing Reflexivity Reflexivity became a guiding principle in my qualitative research journey, helping me navigate the complexities of human interaction and narrative exploration. I recognized that every gesture, response, and non-verbal cue carried significance, and I needed to decode these subtleties to comprehend the holistic context. It dawned on me that unresolved personal biases and emotions hindered genuine understanding. To progress, I needed to address these internal conflicts. The transformation was gradual, driven by lessons from classroom conversations, encounters with a mentor, and self-reflection. My understanding of myself, my research, and my research subjects became enriched. Rediscovering Purpose and Empowerment I unearthed a newfound sense of purpose and empowerment as I embraced reflexivity. Acknowledging my weaknesses and strengths, I found the courage to strategize, become more positive, and tackle challenges head-on. The mentorship of a professor-researcher who spoke at a conference left a lasting impact on me. Her insights and guidance led me to re-enrol in the PhD program and ignited a passion for qualitative research. Her teachings and her own journey inspired me to persevere, even in the face of institutional changes and demanding schedules. Deepening Research Practice Through this transformative journey, I realized that being a competent qualitative researcher demanded a curious and open-minded attitude. Delving deeper into lines of inquiry and adapting to diverse personalities became essential. Effective communication, keen observation, and active listening emerged as indispensable tools. In contrast to quantitative research’s reliance on statistics, qualitative research’s collaborative nature requires engagement and participation to uncover hidden nuances. This realization made me appreciate the power of collaborative exploration and the collective interpretation of experiences. Empowering Society’s Voices The realization that qualitative research unveils the essence of real-world events and experiences holds the potential to bring about transformative change. This understanding extends beyond surface-level observations, allowing us to explore the fundamental underpinnings of societal issues. Constructivism and post-positivism took on deeper meanings as I embraced the richness of naturally occurring phenomena, fostering a sense of environmentalism and artistic appreciation. Conclusion Reflecting upon my journey, I understand that embracing reflexivity and qualitative research has transformed my perspective, ignited my passion, and equipped me to face challenges with newfound confidence. With a focus on investigating life’s complexities, I aim to amplify silenced voices and contribute to a better society. The lessons learned extend beyond research methodologies, encapsulating a profound transformation of self and purpose.